Model for calculating refractive index from energy gap for binary and ternary chalcopyrite semiconductors - Farooque, Umar; Rashid, Tarique; Kumar, Ajay; Rabbani, Shadab; Ahmad, Faiz (Vietnam Journal of Science and Technology, 2025)
Based on the energy gap ( ) data, a simple model has been proposed for the calculation of refractive index ( ) of the binary semiconductors, oxides, halides, insulators, and ternary chalcopyrite semiconductors of , and  families. The refractive index values of the above-mentioned semiconductor materials have been calculated by utilizing the proposed model. Further, the reported values of the refractive index by different models in the literature for the considered semiconductor materials have also been mentioned for the comparison purpose. Moreover, the values of the average percentage deviations have been calculated for all models. The obtained values of the average percentage deviation for the proposed model is almost lowest compared to that of the reported models. Additionally, most of the reported models have not mentioned the values of refractive index for different semiconductor materials, while the proposed model has been utilized to calculate the values of refractive index for a wide range of semiconductor materials. Thus, it validates the suitability of our proposed model in the estimation of refractive index values of different technologically important materials.